Pembelajaran Cerdas ( Smart Teaching ) dalam Metode TANDUR dan Motivasi Belajar Siswa MI Miftahul Ulum Ngoro Mojokerto - Fadilah, Nur; Layinah, M; Hafid, Ainun (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The purpose of this study was to analyze motivation, implementation of the TANDUR method in the subject of Islamic Cultural History at MI Miftahul Ulum Ngoro-Mojokerto. This study also wanted to know the supporting and inhibiting factors in implementing the TANDUR method in the subject of Islamic Cultural History at MI Miftahul Ulum Ngoro-Mojokerto. Classroom action research method by implementing four stages, namely planning, action, observation and reflection. The results of the study showed that the application of the TANDUR method was able to increase students' motivation to study, especially in Islamic Cultural History subjects. (SKI). The supporting fact in the use of the TANDUR method is the availability of technological facilities, while the inhibiting fact is that some teachers are still unable to compile learning tools.